Nitrate and Inhibition of Ruminal Methanogenesis: Microbial Ecology, Obstacles, and Opportunities for Lowering Methane Emissions from Ruminant Livestock - Yang, Chengjian; Rooke, John A.; Cabeza, Irene; Wallace, Robert J. (Frontiers in Microbiology, 2016)
Ruminal methane production is among the main targets for greenhouse gas (GHG) mitigation for the animal agriculture industry. Many compounds have been evaluated for their efficacy to suppress enteric methane production by ruminal microorganisms. Of these, nitrate as an alternative hydrogen sink has been among the most promising, but it suffers from variability in efficacy for reasons that are not understood. The accumulation of nitrite, which is poisonous when absorbed into the animal’s circulation, is also variable and poorly understood. This review identifies large gaps in our knowledge of rumen microbial ecology that handicap the further development and safety of nitrate as a dietary additive. Three main bacterial species have been associated historically with ruminal nitrate reduction, namely Wolinella succinogenes, Veillonella parvula, and Selenomonas ruminantium, but others almost certainly exist in the largely uncultivated ruminal microbiota. Indications are strong that ciliate protozoa can reduce nitrate, but the significance of their role relative to bacteria is not known. The metabolic fate of the reduced nitrate has not been studied in detail. It is important to be sure that nitrate metabolism and efforts to enhance rates of nitrite reduction do not lead to the evolution of the much more potent GHG, nitrous oxide. The relative importance of direct inhibition of archaeal methanogenic enzymes by nitrite or the efficiency of capture of hydrogen by nitrate reduction in lowering methane production is also not known, nor are nitrite effects on other members of the microbiota. How effective would combining mitigation methods be, based on our understanding of the effects of nitrate and nitrite on the microbiome? Answering these fundamental microbiological questions is essential in assessing the potential of dietary nitrate to limit methane emissions from ruminant livestock.